Effects of Grinding Corn through a 2-, 3-, or 4-High Roller Mill on Pig Performance and Feed Preference of 25- to 50-lb Nursery Pigs - J. T. Gebhardt; J. A. De Jong; M. D. Tokach; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband; K. F. Coble; C. R. Stark; C. K. Jones; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2015)
A total of 410 pigs were used in two experiments to determine the effects of grinding corn through various roller mill configurations on feed preference and performance of nursery pigs. In Exp. 1, 320 pigs (DNA 400 × 200, initially 23.6 lb) were randomly allotted to 1 of 4 dietary treatments with 16 pens per treatment and 5 pigs per pen for a 21-d growth trial. The 4 dietary treatments used the same corn-soybean meal-based formulation that was mixed from the same batch of ingredients. Corn was ground through the same 4-high roller mill, but using different roller configurations. Experimental diets were: (1) feed with corn fraction ground to 650 μm using 2 sets of rolls (2-high), (2) feed with corn fraction ground to 495μm using 3 sets of rolls (3-high), (3) feed with corn fraction ground to 340 μm using 4 sets of rolls in a fine grind configuration (4-high fine), and (4) feed with the corn fraction ground to 490μm using 4 sets of rolls in a coarse grind configuration (4-high coarse). The same roller mill was used for all configurations with the appropriate lower rolls completely open when using the 2 or 3 sets of rolls configurations. In Exp. 2, 90 pigs (PIC 327 × 200, initially 27.0 lb) were randomly allotted to one of three diet comparisons to determine feed preference. The 3 diets used were from the 2-high roller mill configuration or the fine or coarse 4-high roller mill ground corn. Each pen contained 2 feeders, each containing 1 of the 3 treatment diets. The 3 diet comparisons tested were 2 vs. 4-high fine (1 vs. 3), 2-high vs. 4-high coarse (1 vs. 4), and 4-high fine vs. 4-high coarse (3 vs. 4). Feeders were rotated once daily within each pen for the 7-d study. There were 5 pigs per pen, and 6 pens per treatment. In Exp. 1, there were no differences (P>0.05) in ADG, ADFI or F/G among roller mill configurations (Table 5). Similarly, no differences were observed (P>0.05) for caloric efficiency or economics among roller mill configurations. In Exp. 2, when given a choice, pigs consumed 67% (P<0.05) of the diet containing corn ground through the 2-high roller mill compared to only 33% from the diet containing 4-high fine corn (Table 6). There was no difference (P>0.05) in feed consumption of 2-high roller mill corn and the diet manufactured with the 4-high roller mill in a coarse configuration (50.3 to 49.7%, respectively). However pigs consumed 63% (P<0.05) of the diet manufactured using the 4-high roller mill in a coarse configuration and only 37% from the diet using the 4-high mill in a fine grind configuration. In the study, roller mill configuration had a significant impact on feed preference in nursery pigs, most likely as a result of differences in particle size. However, when nursery pigs did not have the choice between diets, there were no differences in gain, feed consumption, feed efficiency, or economics. Therefore, the study did not indicate a benefit in nursery pig performance or economic return when particle size was reduced below 650μm.
Keywords: roller mill; nursery pigs; feed preference; particle size